Resilience and ductility of Oxy-fuel HAZ cut - A. Martín-Meizoso,; J. Aldazabal,; J.L. Pedrejón; S. Moreno (Fracture and Structural Integrity)
Cutting processes affect the material to a deeper or shallower attached-to-the-cut zone. Its microstructure, its hardness and mechanical properties are changed. Also the cutting process introduces surface roughness and residual stresses. In most cases it is recommended to remove this region by grinding, in order to keep a smoother surface, free from the above mentioned effects. This work presents the characterization results of the Heat Affected Zone (HAZ) of a steel plate of grade S460M, with a thickness of 25 mm, cut by flame oxyfuel gas cutting. The HAZ microstructure is observed (and the depth of the HAZ measured), the hardness profile and the stress vs. strain curves until fracture are measured by testing micro-tensile samples, instrumented with strain gauges. Micro-Tensile specimens are 200 microns in thickness and were obtained from layers of the HAZ at different distances from the oxy-fuel cut. The obtained stress-strain curves are compared with the hardness measurements and the observed metallography.